EFEKTIVITAS PENGGUNAAN MEDIA ASEMBLER EDU DALAM MENINGKATKAN PEMAHAMAN KONSEP PESERTA DIDIK PADA MATERI SISTEM PEREDARAN DARAH - Fitriani, Fitriani (PENA KREATIF : JURNAL PENDIDIKAN, 2026)
This study was conducted to determine the effectiveness of using Assemblr Edu learning media in improving students’ conceptual understanding of the circulatory system. This research employed an experimental method with a quasi-experimental design, specifically the pretest–posttest non-equivalent control group design. The study was carried out in Grade VIII at SMP Negeri 4 Seponti. The research population consisted of all Grade VIII students, with a total sample of 32 students. The research instrument used was a written test consisting of five essay questions. The data were analyzed using prerequisite tests, namely the normality test and homogeneity test. Hypothesis testing was conducted using the paired sample t-test with the assistance of IBM SPSS version 25. The results showed that the significance value (Sig. 2-tailed) was 0.000 < 0.05, indicating that H₀ was rejected and H₁ was accepted. These findings demonstrate that Assemblr Edu learning media is effective in improving students’ conceptual understanding of the cardiovascular system material.